Reframing African political economy: Clientelism, rents and accumulation as drivers of capitalist transformation - Hazel Gray; Lindsay Whitfield (London School of Economics and Political Science (LSE), Department of International Development, 2014)
This paper examines the underlying assumptions about socioeconomic transformation within the dominant approaches to the political economy of African countries. We argue that the dominant frameworks within African Studies miss important aspects of contemporary processes of socioeconomic change. As an alternative, we argue that political settlements theory provides a better theoretical framework through which to understand contemporary African political economy. We set out the major assumptions and trace the intellectual landscape in which to locate the Political Settlement approach in a way which highlights the distinctions with existing dominant approaches in African studies. The paper then goes on to explain the underlying assumptions about capitalist transformation and the drivers of clientelism embedded within a political settlements approach. We explain how variations in politics and clientelism stem from variations in the distribution of power across countries and how these variations affect the process of capitalist transformation. The paper outlines the implications of the Political Settlements approach for the study of African political economy. It argues that there is not one African political economy, because the distribution of power is quite diverse across African countries; rather, what has accounted for many similarities in African experiences is to be found in the size and capabilities of domestic capitalists and the historical construction of relations between domestic capitalists and the state over time. In concluding, we propose the contours of a new research agenda based on the Political Settlements approach.
Keywords: 330; Socioeconomic transformation; Clientelism; Africa; Political Economy; Neo-patrimony